PENGARUH CITRA PERUSAHAAN DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA JASA PERHOTELAN ( KASUS HOTEL BENTENG PEKANBARU ) - Deli Darlina; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the influence of corporate image and service quality oncustomer loyalty at the Hotel Fort Pekanbaru. The company's image as a variable (X1) quality ofservice as a variable (X2) and customer loyalty as (Y).The method in this research is descriptive and quantitative using SPSS 20, where sampleswere used that guests staying more than 3 times in the Hotel Fort Pekanbaru with respondents asmany as 99 people. To determine the number of samples used slovin formula, as well as asampling technique by purposive sampling. Data collection through questionnaires andinterviews.Results of analysis using multiple linear regression, t test and f test so that it can be seenthat the variable corporate image positive effect on customer loyalty, that the provision ofquality services significant effect on customer loyalty and significant influence of the company'simage and service quality on customer.Keywords: Corporate Image, Service Quality and Customer Loyaltyloyalty.